Nitric oxide-mediated modulation of reproductive resilience under cold stress in chickpea - Kaur, Sarbjeet; Padhiar, Deeksha; Jha, Uday Chand; Kumar, Sanjeev; Sharma, Kamal Dev; Parida, Swarup Kumar; Siddique, Kadambot H. M.; Prasad, P. V. Vara; Nayyar, Harsh (Frontiers in Plant Science, 2025)
Chickpeas are particularly sensitive to cold stress during the reproductive phase, which can significantly impair pod set and yield. This study examined the role of sodium nitroprusside (SNP), a nitric oxide (NO) donor, in mitigating cold-induced reproductive damage in cold-tolerant (CT) and cold-sensitive (CS) chickpea genotypes. After 100 days of outdoor growth, plants were subjected to cold stress (15/8°C day/night; 12 h photoperiod) for 21 days in walk-in growth chambers during the reproductive stage of development. Control plants were maintained at 25/15°C day/night temperature. SNP treatment (1 mM) was applied exogenously each time, first two days prior to stress onset and then at seven-day intervals (three applications total). Cold stress significantly lowered endogenous NO levels in leaves, anthers, and ovules, particularly in CS genotypes, thereby leading to reduced pollen viability and germination. SNP treatment restored NO and improved reproductive performance, with stronger responses in the CS than the CT genotype. For instance, pollen germination increased by 57.9% in CS versus 17.6% in CT, and pollen viability increased by 28.0% and 13.1%, respectively. Enhanced anther function resulted in a 157.2% increase in pod set and 62.0% higher seed yield in CS. SNP also improved physiological traits, including a 43.9% increase in cellular viability, 18.6% in stomatal conductance, and 41.9% in chlorophyll content in CS genotypes. Cryoprotectants (proline, trehalose, and sucrose) accumulated in anthers, reinforcing cold resilience, while oxidative stress was simultaneously alleviated through reduced malondialdehyde, hydrogen peroxide, and electrolyte leakage, together with the upregulation of both enzymatic (superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APx), and glutathione reductase (GR)) and non-enzymatic (ascorbic acid (ASC) and reduced glutathione (GSH)) components. Notably, CS genotypes showed more pronounced improvements from SNP application than CT genotypes, particularly in terms of reproductive success and yield-related traits. These findings highlight the potential of NO donors, such as SNP, to enhance cold tolerance in chickpeas, with promising implications for safeguarding productivity under low-temperature stress, especially in sensitive cultivars.